Theoretical Investigation of Anhydrofusarubin: Structural and Optical Properties - Dmitrii Pankin; Anastasia Povolotckaia; Mikhail Smirnov; Evgenii Borisov; Anatoly Gulyaev; Alexey Dorochov; Vasiliy Novikov; Sergey Kuznetsov; Oleg Noy; Sergey Belousov; Maksim Moskovskiy (Crystals, 2023)
Anhydrofusarubin is a naphthoquinone pigment synthesized by a number of Fusarium genus fungi. Being a biologically active substance, it demonstrates promising antibiotic properties and rather good hypothetical effectiveness against certain types of cancer. In this regard, an important task arises to study the structural properties and spectral manifestation of Anhydrofusarubin in order to identify and characterize this substance in terms of synthesis and application purposes. In this regard, the aim of the article was to study the structure of the Anhydrofusarubin molecule and its structure-property correlation. The density functional theory was used to investigate the optical properties and stability of the molecular structures. The computational results obtained with B3LYP and wb97XD exchange correlation functionals and the triple zeta basis sets were compared with available experimental data. In addition to the ground state structure, a tautomer with slightly higher energy (by 0.78–0.9 kcal/mol) and a relatively small potential barrier was found. Also, the investigation of flexibility of the pyran ring reveals the presence of two conformational enantiomer forms, being in good agreement with the recent experimental data on the crystal structure. The vibrational and UV-visible absorption spectra were simulated and interpreted.